The Effect of Supervision and Communication on Employee Performance in Satpol PP Offices in Bengkulu Selatan District - Wanda Syah Putra; Neri Susanti; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the effect of supervision and communication on employee performance at the Satpol PP Office in South Bengkulu Regency. The sample in this study 44 employees who have become the State Civil Apparatus (ASN) at the Satpol PP Office in South Bengkulu Regency. Data collection using a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testing. The results of multiple linear regression calculations obtained the multiple linear regression equation Y = 3,762 + 0,510X1 + 0,420X2. The coefficient of determination of the Adjusted R square value is 0.487. This means that X1 (supervision) and X2 (communication) have an effect on performance (Y) by 48.7% while the remaining 51.3% is influenced by other variables not examined in this study. The results of the F test show that the significance is 0.000 <0.05. Because the significance level is below 0.05, it indicates that together X1 (supervision) and X2 (communication) have a positive and significant effect together on performance (Y). Supervision has a positive and significant effect on performance, communication has a positive and significant effect on performance because the significant value is smaller than 0.05.